A capable numerical scheme for solving nonlinear Volterra delay integral equations of the third kind - Rohollah Ghaedi Ghalini; Esmail Hesameddini; Hojatollah Laeli Dastjerdi (Results in Applied Mathematics)
In this paper, a class of nonlinear Volterra delay integral equations of the third kind (VDIEs) is approximated by an efficient manner. At first, by using some conditions the existence and uniqueness of the solution is discussed based on the nonlinear cordial Volterra integral operators. Moreover, its convergence analysis is shown by using interpolation properties through some theorems and lemmas. Also, some examples are given and the results are compared with their exact solutions to demonstrate the reliability and capability of this algorithm.